Scopping Review: Peran regulasi emosi remaja awal dalam mengatasi stress: Scopping Review: The role of early adolescent emotion regulation in coping with stress - Safadila, Naura; Qonitatin, Novi (Psikologi UHAMKA, 2025)
Early adolescence is an important developmental phase characterized by physical, psychological and social changes. At this stage, adolescents often experience difficulties in managing stress, especially due to academic demands and social dynamics, which are closely related to emotion regulation. This study aims to explore the role of emotion regulation in stress management in early adolescence through a scoping review method of the last five years of literature. Data were obtained from Scopus and Science Direct databases using the keywords “emotion regulation” AND “stress management” AND “early adolescence”. Of the 721 articles found, 12 articles met the inclusion criteria and were analyzed using the PRISMA method. Results showed that emotion regulation skills, social support, self-confidence and secure attachment play an important role in helping adolescents manage stress. However, challenges such as difficulty expressing emotions, negative social environment influences, and socioeconomic factors exacerbate the condition. Therefore, a holistic approach that emphasizes strengthening emotion regulation and creating a supportive social environment is needed. Keywords: emotion regulation, adolescent stress, stress management, social support